2008
DOI: 10.1098/rspb.2008.0457
|View full text |Cite
|
Sign up to set email alerts
|

Life history constrains biochemical development in the highly specialized odontocete echolocation system

Abstract: The vertebrate head has undergone enormous modification from the features borne by early ancestors. The growth of skull bones has been well studied in many species, yet little is known about corresponding soft tissue development. Among mammals, some of the most unusual examples of cranial evolution exist in the toothed whales (odontocetes). Specialized fat bodies in toothed whale heads play important roles in sound transmission and reception. These fat bodies contain unique endogenous lipids, with favourable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Fats within the odontocete mandible are similar to seawater in acoustic impedance, suggesting these fat bodies preferentially conduct sound to the inner ear (Varanasi and Malins, 1972). Biochemical analyses of the lipids within odontocete heads show that the 'acoustic fats' have a specific topographical arrangement within the lower jaw, perhaps affecting sound speed to channel incoming sound to the ears (Koopman et al, 2006;Koopman and Zahorodny, 2008). The jaw hearing hypothesis is supported by intracranial-recorded evoked potential and cochlear action potential studies, which demonstrated good hearing sensitivity from the dolphin lower jaw (Bullock et al, 1968;McCormick et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Fats within the odontocete mandible are similar to seawater in acoustic impedance, suggesting these fat bodies preferentially conduct sound to the inner ear (Varanasi and Malins, 1972). Biochemical analyses of the lipids within odontocete heads show that the 'acoustic fats' have a specific topographical arrangement within the lower jaw, perhaps affecting sound speed to channel incoming sound to the ears (Koopman et al, 2006;Koopman and Zahorodny, 2008). The jaw hearing hypothesis is supported by intracranial-recorded evoked potential and cochlear action potential studies, which demonstrated good hearing sensitivity from the dolphin lower jaw (Bullock et al, 1968;McCormick et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…N 2 solubility in toothed whale blubber (melon) and reception (mandibular fat bodies) of high frequency sound. One of the characteristic features of the acoustic fats is that they all contain some amount of WE (varying from ~5-10% in porpoises to >90% in beaked whales) Koopman and Zahorodny, 2008), even if the blubber of the species in question does not. Necropsies of stranded whales have suggested that the acoustic fat bodies might be vulnerable to the formation of gas bubbles under certain conditions (Fernández et al, 2005;Jepson et al, 2003).…”
Section: Physiological and Biological Implications Of The Datamentioning
confidence: 99%
“…The following temperature program was used: 65°C for 2min, hold at 165°C for 0.40min after ramping at 20°Cmin -1 , hold at 215°C for 6.6min after ramping at 2°Cmin -1 , and hold at 250°C for 5min after ramping at 5°Cmin -1 . Up to 80 different fatty acids/alcohols were identified (see Koopman, 2007;Koopman and Zahorodny, 2008). Peak identification was based on comparisons of retention time to standards (Nu Chek Prep) and known samples.…”
Section: Lipid Composition Analysismentioning
confidence: 99%
“…Studies on species with different life-history timelines indicate that the attainment of an 'adult-like' composition of acoustic lipids coincides with the timing of nutritional independence (i.e. the duration of maternal care; Koopman and Zahorodny, 2008).…”
Section: %mentioning
confidence: 99%